PENGARUH SUBSTITUSI TEPUNG KACANG MERAH TERHADAP KUALITAS BOLU GULUNG - Anggraini, Dessy; Syarif, Wirnelis; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research was motivated by the use of red beans in the community isstill small. This study was aimed to analyze the effect of substitution of red beanflour as much as 15%, 30%, 45% of the amount of flour used to the quality ofshape, color, aroma, flavor, and texture of the roll cake. Type of research waspure experiment (true experiment) by the method of completely randomized designwith three replications and the number of panellists 30 people. The results showedthat F count> F table so that substitution of red bean flour on the quality of aneffect on the quality of fresh rolls neat shape and form circular, yellow, fragrantflavor, sweetness and flavor of red beans, creamy texture, but has no effect on thequality of the uniform shape of the sponge the rolls and the best value found onthe substitution of 15% (X1).Keywords: Red Bean Flour, Roll Cake, Quality.